Biomechanical performance of post-and-cores of polyetheretherketone and its composites - Biyao Wang; Minghao Huang; Kaige Zhang; Yan Xu; Xinwen Zhang; Liye Shi; Xu Yan (BMC Oral Health)
Abstract Background Polyetheretherketone (PEEK) and its fiber-reinforced composites have been indicated as ideal post-and-cores materials due to its mechanical properties. However, the laboratory evidences of post-and-cores restored with fiber-reinforced PEEK are lacking. Materials and methods A total of 120 extracted mandibular premolars were treated endodontically and divided into six groups restored with different post-and-core materials (N = 20): (1) prefabricated quartz fiber-reinforced composite (QFRC), (2) polymer-infiltrated ceramic (PIC), (3) cobalt chromium (CoCr), (4) PEEK, (5) 30% glass fiber-reinforced PEEK (GFR-PEEK), and (6) 30% carbon fiber-reinforced PEEK (CFR-PEEK). Stress distribution was analyzed by finite element analysis (FEA). Then, each group was then divided into two subgroups (n = 10): static loading test and fatigue loading test. The static failure load (SFL) was analyzed by one-way analysis of variance (ANOVA) with least-significant difference (LSD) multiple comparison tests. The fatigue failure load (FFL) and cycles for failure (CFF) were evaluated by Kaplan-Meier survival analysis (P < 0.05). Results Groups PEEK, GFR-PEEK, and CFR-PEEK exhibited lower maximum peak principal stress and better stress distribution than Group CoCr. The SFL of Groups PEEK and QFRC did not differ from each other, and both were lower than those of Groups CoCr, GFR-PEEK, and CFR-PEEK. In the fatigue loading test, Group CoCr exhibited the best survival; however, with the progression of fatigue, the survival probabilities of Groups PEEK and its composites were close to that of Group CoCr. In all groups apart from Group CoCr, the rate of repairable failure modes was higher than that of irreparable ones. Conclusions Customized post-and-cores manufactured with PEEK and its fiber-reinforced composites showed superior biomechanical performance, making them potential alternatives for the restoration of massive tooth defects. Clinical relevance This study provides a theoretical basis for clinicians to select post-and-core materials for different root canal morphology residual roots and helps to reduce the occurrence of complications such as root fracture and post core debonding.